Incidence of the new coronavirus disease in Brazil in periods before and after the elections and the governmental influence on the progression of cases (Research, Society and Development, 2022)
The research aimed to carry out an epidemiological survey comparing the cases of COVID-19 in moments before and after the electoral period in Brazil, pointing out the influences of the federal public administration in the increase in incidence and consequent mortality. This is a quantitative epidemiological study with a critical approach, based on secondary data from the Information and Notifiable Diseases System (SINAN) found in the Information Technology Department of the Unified Health System (DATASUS), whose data are from March to December 2020, and January to March 2021 were selected. We analyzed 12,748,747 confirmed cases of COVID-19 grouped in incidence by month in the period evaluated and compared them by the non-parametric Kruskal-Wallis method, where a P value